Efficacy of Sucralfate in Reflux Disease in comparison to H2 – Receptor Antagonist: A Meta-Analysis of Randomized Trials - Bedre, Renesh; Raj, Utkarsh; Varadwaj, Pritish (Biology, Engineering, Medicine and Science Reports)
Background and Aim: Reflux esophagitis is characterized by the erosions of esophagus due to gastric acids. H2 -Recptor antagonists are considered as effective therapy. We compared sucralfate with H2 -receptor antagonist for treatment of reflux esophagitis. Methods: Seven studies are selected from different databases (PUBMED, MEDLINE, COCHRANE LIBRARY, CINAHL etc.) comparing the treatment of sucralfate with H2 -receptor antagonists (cimetidine and ranitidine). All studies selected are randomized controlled clinical trials. We applied inclusion and exclusion criteria for selection of studies. We also checked for heterogeneity and publication bias. We calculated odds ratio and 95% confidence interval for each study. We searched for national library of medicine’s clinical trial registry for any unpublished data. Results: Seven studies consisting of 319 patients finally selected for meta-analysis. We evaluated confidence interval and odds ratio for each study. None of the study show statistical significant result (p>0.05). The overall effect obtained by combining studies shows no statistical significant result (OR= 1.357, 95% CI=0.834 to 2.206, P-value=0.219, I2 =0) between sucralfate and H2 -recptor antagonist. There is no heterogeneity among the studies (I2 =0, χ2 =4.8). Conclusion: We can conclude that sucralfate is an effective alternate for treatment of reflux disease.